Research about training monitoring during different training periods in Chinese elite swimmers - Qiu, J.; Li, M.; Yi, L.; Hou, Z.; Yang, F.; Yao, Y. (Exercise Biochemistry Review, 2018)
Objective Training monitoring has become an integral component of total athlete training. Systematically monitoring the physiological and biochemical variables related to performance helps coaches and athletes to measure the effectiveness of their training programs and decide how to revise or update those programs, especially in swimming training. The key purpose of this study is to evaluate the physical function characteristics during preparation season and stress response during competition training sessions in 2017, and provides the helpful data for scientific training for the implementation of the preparation process.